Effect of Intermediate Elastic Support on Vibration of Functionally Graded Euler-Bernoulli Beams Excited by a Moving Point Load - Buntara Sthenly Gan; Nguyen Dinh Kien; Le Thi Ha (Journal of Asian Architecture and Building Engineering, 2017)
The effect of intermediate elastic support on the vibration of functionally graded Euler-Bernoulli beams excited by a moving point load is studied. The material properties of the beams are assumed to vary in the thickness direction of the beams by a power function. Governing equations of motion that take into account the shift in the physically neutral surface position, are constructed using Hamilton′s principle. A finite element model is developed and employed in computing the dynamic response of the beams. The influence of the stiffness and position of the elastic support on the dynamic characteristics of the FGM beams is examined and highlighted.